1993
DOI: 10.1111/j.1460-9568.1993.tb00918.x
|View full text |Cite
|
Sign up to set email alerts
|

GAP‐43, aFGF, CCK and α‐ and β‐CGRP in Rat Spinal Motoneurons Subjected to Axotomy and/or Dorsal Root Severance

Abstract: The mRNA levels for growth-associated protein 43 (GAP-43), acidic fibroblast growth factor (aFGF), alpha- and beta-calcitonin gene-related peptide (CGRP), cholecystokinin (CCK) and choline acetyltransferase (ChAT) in rat lumbar spinal motoneurons were studied by in situ hybridization 1, 5 and 21 days and 20 weeks following unilateral peripheral nerve sectioning, ventral rhizotomy or dorsal rhizotomy. Furthermore, CGRP- and aFGF-like immunoreactivities in the ventral horn were studied using immunohistochemistry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0
11

Year Published

1997
1997
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 59 publications
4
31
0
11
Order By: Relevance
“…Various spinal and cranial nerve motoneurons do express protein and mRNA of FGF-1 Piehl et al, 1993) and of FGF-2 (Grothe et al, 1991a;Gonzalez et al, 1995). In line with these data is the first demonstration of the FGF-2 mRNA in hypoglossal motoneurons in this study in addition to the previously reported presence of FGF-2 protein in hypoglossal motoneurons Grothe and Janet, 1995).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Various spinal and cranial nerve motoneurons do express protein and mRNA of FGF-1 Piehl et al, 1993) and of FGF-2 (Grothe et al, 1991a;Gonzalez et al, 1995). In line with these data is the first demonstration of the FGF-2 mRNA in hypoglossal motoneurons in this study in addition to the previously reported presence of FGF-2 protein in hypoglossal motoneurons Grothe and Janet, 1995).…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, FGFR1 protein and mRNA are highly expressed by hypoglossal motoneurons, as previously demonstrated for other motoneurons as well (Wanaka et al, 1990;Gonzalez et al, 1995;Grothe and Janet, 1995). In contrast to FGF-1, which was not affected after peripheral nerve axotomy (Piehl et al, 1993), both FGF-2 protein and mRNA are changed after hypoglossal nerve lesion. A temporary reduction of FGF-2 protein was followed by a reexpression of FGF-2 11 days after hypoglossal nerve axotomy .…”
Section: Discussionmentioning
confidence: 50%
“…In line with this, CGRP has been involved in the formation of synaptic processes (Sala et al, 1995). Increased CGRP staining has been shown to persist for a long time, and to be still evident when nearly complete reinnervation has been achieved, even when levels of neurotrophin receptors have returned to control levels (Piehl et al, 1993). Therefore, the fact that CGRP protein was expressed in extraocular motoneurons after lesion might suggest that a process of axonal regrowth and reinnervation has been at least initiated (Fig.…”
Section: Induction Of Cgrp Expression By Axotomymentioning
confidence: 87%
“…In motoneurons, a reduction in choline acetyltransferase (ChAT) expression, an enzyme involved in the synthesis of the neurotransmitter acetylcholine, often occurs after nerve damage (Lams et al, 1988;Matsuura et al, 1997;Wang et al, 1997). In contrast, other molecules like calcitonin gene-related peptide (CGRP), a protein related to rearrangement of synaptic connections, increase their expression after lesion (Calderó et al, 1992;Borke et al, 1993;Piehl et al, 1993;Fukuoka et al, 1999).…”
mentioning
confidence: 96%
“…Compared to other neuronal types, motor neurons contain high levels of FGF-1 [35][36][37] , which represent approximately 0.1% of soluble protein in the cytoplasmic compartment [35] . FGF-1 levels in motor neurons are altered following spinal cord injury or nerve lesions [38,39] , which might be due to an increased rate of release. FGF-1 is not released by a classical secretion pathway but rather by an alternative mechanism triggered by cell damage.…”
Section: Fibroblast Growth Factor-1 Induces Astrocyte Activationmentioning
confidence: 99%